APPLICATION OF GEOELECTRIC METHODS FOR GEOTHERMAL EXPLORATION - Nawwaaf, Ahmad
The geoelectric method is one of the geophysical methods that is often used in geothermal exploration. The resistivity contrast between the geothermal system and the surrounding rock makes the resistivity geoelectric method very good in determining the subsurface geological structure in geothermal exploration. This study aims to determine the subsurface resistivity structure so that it can estimate the area that has a geothermal reservoir. In this study, 1-D and 2-D inversion modeling were carried out on 27 geoelectric sounding data so that resistivity values were obtained that represented the structure of the subsurface layer. The results showed that there are areas that have geothermal potential which is characterized by the presence of geothermal manifestations in the area.